ATMOSPHERIC AND OCEANIC PATTERNS RELATED TO DRY EVENTS IN THE AMAZON BASIN DURING 1982/83, 2004/05 AND 2009/10 - Vargas, Franci Flores (2017)
This study aimed to determine the atmospheric and oceanic patterns related to changes in precipitation over the Amazon basin during the episodes of extreme drought occurred in the years of 1982/83, 2004/2005 and 2009/10. Data from the zonal and meridional components of the wind vector, wind speed, omega, specific humidity, precipitation and sea surface temperature was used. The data was obtained from the reanalysis-2 NCPE/NCAR (except for the variable precipitation which was obtained from the CMAP). The anomalous composition method was used to determine the atmospheric and ocean fields that were characteristic of episodes of intense drought. The results show a deficit in rainfall in the rainy pre-season (SON) in part of the northern region of South America and northeastern Brazil. The lower level of rainfall also persists during the rainy season (December to April). Associated with these anomalous patterns of rainfall, positive anomalies of SST were observed which were similar to El Niño events, followed by anomalous subsidence in the Amazon. In the rainy pre-season, wind divergence over the state of Amazonas and the north of South America was observed. During the rainy season, the divergence in streamlines shows the weakening of the northeast trade winds. In addition, the anomalous divergence of vertically integrated moisture flux reveals consistency with rainfall deficits in theipre and rainy season in the Amazon basin.